2020
DOI: 10.3390/ijms21228669
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/AKT Pathway Is Activated by HGF in NT2D1 Non-Seminoma Cells and Has a Role in the Modulation of Their Malignant Behavior

Abstract: Overactivation of the c-MET/HGF system is a feature of many cancers. We previously reported that type II testicular germ cell tumor (TGCT) cells express the c-MET receptor, forming non-seminomatous lesions that are more positive compared with seminomatous ones. Notably, we also demonstrated that NT2D1 non-seminomatous cells (derived from an embryonal carcinoma lesion) increase their proliferation, migration, and invasion in response to HGF. Herein, we report that HGF immunoreactivity is more evident in the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In this cell line, we already demonstrated that c-Src and phosphatidylinositol 3-kinase (PI3K) pharmacological inhibition abrogates the HGF-dependent increase of cell proliferation, polarized and collective migration, as well as cell invasion. We also found that, surprisingly, c-Src or PI3K pharmacological inhibition, when administered in basal culture conditions, increases NT2D1 invasiveness via an HGF-independent way, highlighting the importance of the microenvironmental cues in modulating cellular responses to pharmacological stimuli [5,8].…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…In this cell line, we already demonstrated that c-Src and phosphatidylinositol 3-kinase (PI3K) pharmacological inhibition abrogates the HGF-dependent increase of cell proliferation, polarized and collective migration, as well as cell invasion. We also found that, surprisingly, c-Src or PI3K pharmacological inhibition, when administered in basal culture conditions, increases NT2D1 invasiveness via an HGF-independent way, highlighting the importance of the microenvironmental cues in modulating cellular responses to pharmacological stimuli [5,8].…”
Section: Introductionmentioning
confidence: 65%
“…NT2D1 embryonal carcinoma cells (American Type Culture Collection (ATCC) were used in this study and cultured as reported in [4,5,8]. Cells, cultured in DMEM (Sigma Aldrich, cat.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…The modulation of cell cannibalism is determined by Jun N‐terminal kinase, EMT, and stem cell‐like markers, which lead to the activation of deceleration programs and drug resistance in vitro 178–180 . In addition, CAF‐derived secretory proteins, such as hepatocyte growth factor (HGF), the ligand of MET, trigger the activation of the PI3K–AKT signaling pathway 181–183 . This pathway endows resistance to BRAF inhibition in melanoma, colorectal, and glial tumor cells 184–187 .…”
Section: Dormant Cancer Cell Resembling Embryonic Diapausementioning
confidence: 99%